Impact of Exposure to Fenitrothion on Vital Organs in Rats - Rasha Abdel-Ghany; Ebaa Mohammed; Shimaa Anis; Waleed Barakat (Journal of Toxicology)
This study was designed to investigate the impact of oral administration of fenitrothion (10 mg/kg) on liver, kidney, brain, and lung function in rats. The effect was studied on days 7, 14, 21, 28, and 42. Our results have shown deterioration in liver function as evidenced by the elevation in serum ALT, AST, ALP, and bilirubin and reduction in albumin and hepatic glycogen. This was associated with a state of hyperglycemia and hyperlipidemia and increased prothrombin time, while hemoglobin content was reduced. In addition, the kidney function was reduced as indicated by the elevation in serum creatinine, uric acid, and BUN, while the serum levels of magnesium, potassium, and sodium were reduced. This study also showed an impairment in brain neurotransmitter (elevated 5-HT, glutamate, GABA, and reduced dopamine and norepinephrine level). This was associated with a reduction in the barrier capacity in brain and lung. Fenitrothion also caused a decrease in cholinesterase activity in serum, lung, and brain activity associated with a state of oxidative stress in all tested organs and hyperammonemia. These results support the hazards of pesticide use and shows the importance of minimizing pesticide use or discovering new safe pesticides.